FOREIGN EXPERIENCE IN FORMING FINANCIAL TRANSFERS AND PAYMENT SYSTEMS IN THE NEW UZBEKISTAN - Normamatov, I.B (THE INNOVATION ECONOMY, 2024)
In the article, scientific proposals aimed at forming an innovation-oriented economy in the country in a short period of time and creating conditions for the wide introduction of innovations have been developed. Ensuring the liquidity and financial stability of companies is one of the necessary conditions for ensuring their competitiveness. However, the low level of cash supply of the country’s economy, the high cost of products under the influence of inflation and devaluation hinder the increase of liquidity and financial stability of companies. The article identifies current issues related to ensuring the liquidity and financial stability of companies in the Republic of Uzbekistan and develops scientific proposals to address them.